Predatory mites of the genus Asca (Acari Ascidae) associated with cultivated crops in the Philippines - De Leon-Facundo, Josephine B.; Corpuz-Raros, Leonila A. (2004)
Philippine predatory mites belonging to Asca von Heyden were taxonomically studied based on existing collections deposited in the Entomological Museum, Museum of Natural History, University of the Philippines Los Baños. A total of 16 species are described in this paper, 10 of which are new to science and 6 are new records for the Philippines. All the reported species are associated with cultivated crops. The new Philippine species brings to a total of 107, the number of Asca species known worldwide. The males of A. craneta de Leon and A. aethiopica Ryke are reported for the first time. Detailed descriptions and illustrations are furnished for all included species. A key to known Philippine species of Asca is provided.
Keywords: Mites; Taxonomy